Topical issues of dabigatran use in combination antithrombotic therapy in patients with acute coronary syndrome and nonvalvular atrial fibrillation - N. A. Novikova; A. S. Shilova («REMEDIUM GROUP» Ltd., 2020)
Atrial fibrillation is the most common heart rhythm disorder. According to various sources, a third of patients with atrial fibrillation also suffer from coronary heart disease. Both acute coronary syndrome and PCI with stable IHD require the prescription of combined antithrombotic therapy, which includes both anticoagulant drugs and disaggregants. A therapeutic dilemma arises: how to balance the extremely high risk of hemorrhagic complications in triple therapy with the risk of ischemic events in dual therapy? Consequently, the combination of atrial fibrillation and ischemic heart disease is not only a complex and widespread problem in terms of the selection of doses and antithrombotic therapy regimes, but is also associated with a significant increase in disability and mortality. Based on data from the PIONEER AF PCI, REDUAL PCI and AUGUSTUS STUDIES, triple therapy should be as short as possible. A tempting alternative seems to be to prescribe dual therapy in 1-7 days after an acute event. According to the ESC recommendations on the treatment of CCS, patients with stable coronary heart disease and atrial fibrillation after CCS are recommended to prescribe three drugs for the period of hospitalization, OAC + Clopidogrel for one year, then only OAC. however, if the risk of stent thrombosis and other ischemic events is high and the risk of bleeding is low, triple therapy can be prolonged. To date, patients requiring anticoagulants in combination with antiaggregants should prefer OAC in doses that have proven effective in preventing stroke in patients with atrial fibrillation (dabigatran 150 mg 2 times a day, apixaban 5 mg 2 times a day and rivaroxaban 20 mg/day).